Comparison of Stress-Strain Relationship for Confined Concrete Using Two-Dimensional Fiber-Based Cross-Sectional Analysis - Nia Dwi Puspitasari; Aulia Dewi Fatikasari (JACEE (Journal of Advanced Civil and Environmental Engineering), 2021)
Stress-strain relationship is the main parameter to identify the strength, ductility and behavior of the structure. Various constitutive models were created in order to simplify the analytical approach of concrete behavior. In this paper, the behavior of reinforced concrete column is modeled using Attard and Setunge’s (1996) and Mander’s (1988) stress-strain constitutive model. The appropriate model for reinforced concrete column was determined based on the existing experimental data. Two-dimensional simulation of reinforced concrete column using fiber-based cross-sectional analysis in MATLAB is sighted. And the performance of the reinforced concrete column from the experimental data is compared with the analysis result from the simulation. There are two comparation methods used in this research. The first method is to compare the linear regression with the reference line. The smallest degree between the linear regression and the referrence line is expected. The second method is to compare the Root Mean Square Defiation (RMSD) value. The smallest RMSD value is expected to get the most suitable constitutive model compared to the experimental data. From the computational process, it was found that Mander’s Constitutive model is preferaed to be used in further analysis problem concerning reinforced concrete column